Exam Anxiety Among Fourth-Year Middle School Students: A Field Study in One of the Middle Schools in the City of M’sila, Algeria - SAMIRA BENAISSI; Dihia Mouffok (Journal of Science and Knowledge Horizons, 2025)
The study aims to identify the level of exam anxiety experienced by fourth-year middleschool students, and to explore differences in anxiety levels based on gender.Gender (male and female). A descriptive method was employed in this study. The Exam Anxiety Scale developed by Dr. OuizahSherikwas used to collect data. The sample included 61 students (23 males and 38 females) who were selected through purposeful sampling from one of the middle schools in the city of M'sila. Statistical treatments (mean, standard deviation and T-test) were employed via SPSS, revealing the following results: - A high level of exam anxiety among fourth-year middle school students. - Significant gender differences in exam anxiety levels favouring females. - Significant differences in exam anxiety levels for repeaters.